Enhancing Contribution of Islamic Higher Education to The Halal Industry in Indonesia: A SWOT Analysis - Waluyo Waluyo; Indah Piliyanti; Taufiq Wijaya (ITB AAS INDONESIA Surakarta, 2023)
The halal industry is one of the ecosystems in the current development of the global Islamic economy. However, unfortunately, the micro and small enterprises in Indonesia is facing obstacles to enter this industry cause of halal certification. In line with the â€œTridarma Perguruan Tinggiâ€ of higher education in Indonesia, Islamic higher education can contribute toward the micro small and medium enterprises to enter the halal market by halal certification process. The paper describes how Islamic higher education in Surakarta identifying strengths, weakness, opportunity and overcoming threats to support the growth of the halal industry. The implication of the study give recommendation by considering strength and opportunity of the institution to take a step by establishing a halal study center first to assist the micro small enterprises around the campus to get halal certification before expanding into a halal inspection agency.